Laser treatment of dilated periorbital veins - V. Yu. Bogachev; V. N. Lobanov; R. Abdosh (Амбулаторная хирургия, 2024)
Delated periorbital veins causing cosmetic discomfort are one of the most common reasons why patients seek treatment at clinics specializing in aesthetic phlebology. The etiology and pathogenesis of the expansion of once-normal veins on the lower and upper eyelids, as well as in the temporal region have not been established. The potential risk factors include various injuries, invasive cosmetic procedures, intake of female sex hormones, exposure to unfavourable environmental conditions, natural skin ageing, heavy sports activities, and sudden body weight loss. It should be noted that dilated periorbital veins can not only cause aesthetic discomfort, but also induce spontaneous haemorrhages into nearby soft tissues. Initially, dilated periorbital veins were treated using various sclerotherapy options or radiofrequency coagulation with a hair-thin electrode. In recent years, owing to the advent of latest laser platforms, especially neodymium activated yttrium-aluminum-garnet (Nd:YAG) ones, percutaneous laser coagulation (PLC) has become the first-choice technique for treating dilated facial veins. The modern long-pulsed Nd:YAG lasers generate 1064 nm laser radiation, which ensures the achievement of target veins located at different depths under the skin's surface, and also demonstrates high affinity towards haemoglobin and its derivatives. In other words, Nd:YAG lasers are the optimal option to treat dilated facial veins, including those in the periorbital region, in patients with any skin phototypes. The multi-application XEO (Cutera) platform designed for photo and laser therapy is the most successful representative of Nd:YAG lasers. The case reports presented in this article highlight the successful treatment of dilated periorbital veins.